A MODERN VIEW OF THE PROBLEMS OF PREVENTION AND TACTICS OF SURGICAL TREATMENT OF BRONCHIAL FISTULAS AFTER LUNG RESECTIONS - Eshonkhodjaev, O.D.; Khudaibergenov, Sh.N.; Khayaliev, R.Ya.; Rakhimiy, Sh.U.; Khusenov, I.N. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
One of the main reasons for unsatisfactory results after lung resections is the development of bronchopleural fistula. Literature on the problem of bronchopleural fistula after forehead and bilobectomy is analyzed. The current trends of the domestic and foreign thoracic surgery in the prevention of bronchopleural fistula development are described in detail. Comparison of various methods of elimination is carried out; modern tactical and technical aspects of the treatment of BPS are described.